Preservation of refrigerated sperm of the mutton snapper with diluents and modified atmosphere - Sanches, Eduardo Gomes; Cerqueira, Vinicius Ronzani (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this study was to evaluate the effect of different diluents at normal and modified atmosphere on the preservation of refrigerated sperm of the mutton snapper Lutjanus analis. Sperm samples o 30 fishes were evaluated for motility rate, motility time, sperm concentration and spermatocrit. For the refrigeration at 4ºC, three different diluents with distinct ionic compositions and pH values were tested at normal and at modified atmospheres (100% oxygen). Afterwards, a fertilization test was accomplished to evaluate the viability of the refrigerated sperm. In the refrigeration experiment, the motility rate and the motility time were maintained appropriate for 72 hours for the extender A (48±7%, 190±26 s) and B (41±4%, 160±22 s) at normal atmosphere. At the modified atmosphere, the sperm quality fell drastically during the first 24 hours, independently of the utilized diluent, and there was no advantage in its use. The fertilization rate with refrigerated sperm for 24 hours, treated with the diluent A, was not different from that of fresh sperm, and both were higher than the one obtained with refrigerated sperm for 48 hours.